Overexpression of MePMEI1 in Arabidopsis enhances Pb tolerance - Zhou, Yangjiao; Li, Ruimei; Wang, Shijia; Ding, Zhongping; Zhou, Qin; Liu, Jiao; Wang, Yajia; Yao, Yuan; Hu, Xinwen; Guo, Jianchun (Frontiers in Plant Science, 2022)
Pb is one of the most ubiquitously distributed heavy metal pollutant in soils, and has serious negative effects on plant growth, food safety, and public health. Pectin methylesterase inhibitors (PMEIs) play a pivotal role in regulating the integrity of plant cell walls; however, the molecular basis by which PMEIs promote plant resistance to abiotic stress remains poorly understood. In this study, we identified a novel PMEI gene, MePMEI1, from Manihot esculenta, and determined its role in plant resistance to Pb stress. The expression of MePMEI1 was remarkably upregulated in the roots, stems, and leaves of cassava plants following exposure to Pb stress. Analysis of subcellular localization revealed that the MePMEI1 protein was localized in the cell wall. MePMEI1 inhibited commercial orange peel pectin methyltransferase (PME), and the expression of MePMEI1 in Arabidopsis decreased the PME content, indicating that MePMEI1 can inhibit PME activity in the cell wall. Additionally, the overexpression of MePMEI1 in Arabidopsis reduced oxidative damage and induced the thickening of cell walls, thus contributing to Pb tolerance. Altogether, the study reports a novel mechanism by which the MePMEI1 gene, which encodes the PMEI protein in cassava, plays an essential role in promoting the tolerance to Pb toxicity by regulating the thickness of cell walls. These results provide a theoretical basis for MePMEI1-mediated plant breeding for increasing heavy metal tolerance, and provide insights into controlling Pb pollution in soils through phytoremediation in future studies.